Morality and responsibility of rulers : European and Chinese origins of the rule of law as justice for world order - Carty, Anthony; Nijman, Janne Elisabeth, 1972- (Oxford : Oxford University Press, 2018)
Arguing that the concept of an 'international rule of law' has a history independent from that of the national rule of law, this book discusses early modern European thought on natural law and justice and Chinese thought on world order and international law. It provides a unique examination of comparative international legal history and philosophy.
This edition previously issued in print: 2018.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on March 1, 2018).
Keywords: Rule of law; International law -- Moral and ethical aspects; Natural law -- History; International law -- Philosophy; International law -- China -- History; International law -- Europe -- History